Photo voltaic integrated multilevel inverter based hybrid filter using spotted hyena optimizer. (December 2021) - Das, Soumya Ranjan; Sahoo, Arun Kumar; Dhiman, Gaurav; Singh, Krishna Kant; Singh, Akansha
Highlights: ● A modular multilevel inverter (MMI) integrated with photovoltaic (PV) is employed in the three-phase system for power quality (PQ) improvement. ● Spotted hyena optimization (SHO) technique is proposed for generating the reference current and tuning the parameter of the PI controller in MMI. ● MMI is designed to supply power produced from the PV system, to the grid and controlling the harmonics and reactive power. ● The auto-scaling incremental conductance (ASINC) based maximum power point tracking (MPPT) technique is employed for drawing maximum power from the solar PV system. Abstract: In this work, a photovoltaic (PV) integrated modular multilevel inverter (MMI) is connected to a three-phase system for power quality (PQ) improvement. The MMI has modular design and high-quality output waveform. Thus, it is widely used for medium and high-power applications. The Spotted Hyena Optimization (SHO) technique is proposed for generating the reference current and tuning the parameter of the PI controller in MMI. The proposed SHO technique is operated under different loading conditions and is compared with the conventional particle swarm optimization (PSO) and firefly optimization (FO) technique. The controlling part of MMI is designed to supply power produced from the PV system to the grid and controlling the harmonics and reactive power. This paper employs an incremental conductance (INC) based maximum power point tracking (MPPT) technique for drawing maximum power. The performance of the proposed technique is analysed using the MATLAB/Simulink tool. Graphical abstract: Image, graphical abstract